Semantic Technology 4th Joint International Conference, JIST 2014, Chiang Mai, Thailand, November 9-11, 2014. Revised Selected Papers - Supnithi, Thepchai; Yamaguchi, Takahira; Pan, Jeff Z.; Wuwongse, Vilas; Buranarach, Marut; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the proceedings of the 4th Joint International Semantic Technology Conference, JIST 2014, held in Chiang Mai, Thailand, in November 2014. The theme of the JIST 2014 conference was "Open Data and Semantic Technology". JIST 2014 conference consisted of main technical tracks including regular paper track (full and short papers), in-use track and special track, poster and demo session, two workshops and four tutorials. The 32 papers in this volume were carefully reviewed and selected from 71 submissions. The paper topics are divided into eight categories: Ontology and Reasoning (7 papers), Linked Data (7 papers), Learning and Discovery (3 papers), RDF and SPARQL (3 papers), Ontological Engineering (3 papers), Semantic Social Web (3 papers), Search and Querying (3 papers) and Applications of Semantic Technology (3 papers).
Ontology and Reasoning -- Revisiting Default Description Logics and their Role in Aligning Ontologies -- On Desirable Properties of the Structural Subsumption-Based Similarity Measure -- A Graph-based Approach to Ontology Debugging in DL-Lite -- Reasoning for ALCQ Extended with a Flexible Meta-modelling Hierarchy -- Employing DL-Lite R-Reasoners for Fuzzy Query Answering -- The Ontology Based Inferences Engine for Veterinary Diagnosis -- An Information Literacy Ontology and its Use for Guidance Plan Design An Example on Problem Solving -- Linked Data -- A Roadmap for Navigating the Life Sciences Linked Open Data Cloud -- Link Prediction in Linked Data of Interspecies Interactions using Hybrid Recommendation Approach -- CURIOS Mobile: Linked Data Exploitation for Tourist Mobile Apps in Rural Areas -- Building of Industrial Parts LOD for EDI - A Case Study -- inteSearch: An Intelligent Linked Data Information Access Framework -- Publishing Danish Agricultural Government Data as Semantic Web Data -- A Lightweight Treatment of Inexact Dates -- Learning and Discovery -- A Multi-strategy Learning Approach to Competitor Identification -- Mining Type Information from Chinese Online Encyclopedias -- RDF and SPARQL -- Graph Pattern based RDF Data Compression -- Optimizing SPARQL Query Processing On Dynamic and Static Data Based on Query Time/Freshness Requirements Using Materialization -- RDFa Parser for Hybrid Resources -- Ontological Engineering -- Ontology Construction and Schema Merging Using an Application-Independent Ontology for Humanitarian Aid in Disaster Management -- A Development of Belief - Culture Ontology and Its Application: In Case Study of Greater Mekong Subregion Culture -- Representations of Psychological Functions of Peer Support Services for Diabetic Patients -- Semantic Social Web -- Personalized Model Combination for News Recommendation in Microblogs -- A Model for Enriching Multilingual Wikipedias using Infobox and Wikidata Property Alignment -- Template-Driven Semantic Parsing for Focused Web Crawler -- Search and Querying -- A Keyword Exploration for Retrieval from Biomimetics Databases -- Choosing Related Concepts for Intelligent Exploration -- A Semantic Keyword Search based on the Bidirectional Fix Root Query Graph Construction Algorithm -- Applications of Semantic Technology -- An Ontology-Based Intelligent Speed Adaptation System for Autonomous Cars -- Ontology based Suggestion Distribution System -- Road Traffic Question Answering System using Ontology.
Keywords: Information storage and retrieval; Artificial intelligence; Database management; Data mining; Application software; Information Storage and Retrieval; Artificial Intelligence; Database Management; Data Mining and Knowledge Discovery; Information Systems Applications (incl. Internet).